Social Media Influence and Electoral Competition. (February 2022) - Shmargad, Yotam; Sanchez, Lisa
Do social media platforms help or hinder democracy? Internet enthusiasts posit that social media could have a democratizing effect by lowering the costs of promotion, while skeptics argue that these platforms replicate or even exacerbate preexisting inequalities. We inform this debate by combining campaign finance and electoral outcome data from the Federal Election Commission with Twitter metrics of candidates who ran in the 2016 U.S. congressional elections. We find that poorer candidates, who spent less than their competitor, performed better if they had indirect influence on Twitter—getting their tweets shared by users whose own tweets are widely shared. The effect of indirect influence on election outcomes was more pronounced in races with larger financial inequities between candidates or fewer total expenses across candidates. Moreover, poorer candidates with indirect influence saw smaller vote gaps than their party's candidate in the same district (in House races) or state (in Senate races) in 2014.